The First Contact of the Venice Biennale with The Ottoman Empire: Request for a Painting from the Ottoman Court Collection - (:unkn) unknown (ISTANBUL UNIV, RESEARCH INST TURKOLOGY, DEPT ART HISTORY, 2020)
The Venice Biennale International Art Exhibition was designed as an organization that would enable the countries of the world to strengthen their national identity in the field of art, and held its first exhibition in 1895. To this event, where the national invitation was compulsory, many countries of Europe and the world were invited for many years, but the Ottoman Empire was never invited to the Venice Biennale exhibitions until the date it officially ended. Although the Ottoman Empire did not nationally participate in the Venice Biennale, it was determined that the representatives of the Venice Biennial made contact with the relevant authorities of the Ottoman Empire in 1914 regarding the Giuseppe De Nittis Retrospective Exhibition to be held within the scope of the Venice Biennale. In the days when the political developments of the period were determinative, this contact, which was established between the two countries, was discussed in the accompaniment of the documents revealed for the first time and evaluated in the article.
Keywords: Venice Biennale; Giuseppe De Nittis; Italy-Ottoman Empire Relations; Antonio Fradeletto